Metformin attenuates pressure overload-induced cardiac hypertrophy via AMPK activation - Fu Yong-nan; Xiao Han; Ma Xiao-wei; Jiang Sheng-yang; Xu Ming; Zhang You-yi (Acta Pharmacologica Sinica, 2016)
Aim: To identify the role of metformin in cardiac hypertrophy and investigate the possible mechanism underlying this effect. Methods: Wild type and AMPKα2 knockout (AMPKα2−/−) littermates were subjected to left ventricular pressure overload caused by transverse aortic constriction. After administration of metformin (200 mg·kg−1·d−1) for 6 weeks, the degree of cardiac hypertrophy was evaluated using echocardiography and anatomic and histological methods. The antihypertrophic mechanism of metformin was analyzed using Western blotting. Results: Metformin significantly attenuated cardiac hypertrophy induced by pressure overload in wild type mice, but the antihypertrophic actions of metformin were ablated in AMPKα2−/− mice. Furthermore, metformin suppressed the phosphorylation of Akt/protein kinase B (AKT) and mammalian target of rapamycin (mTOR) in response to pressure overload in wild type mice, but not in AMPKα2−/− mice. Conclusion: Long-term administration of metformin may attenuate cardiac hypertrophy induced by pressure overload in nondiabetic mice, and this attenuation is highly dependent on AMPK activation. These findings may provide a potential therapy for patients at risk of developing pathological cardiac hypertrophy.